Hydroxygenkwanin Inhibits Class I HDAC Expression and Synergistically Enhances the Antitumor Activity of Sorafenib in Liver Cancer Cells - Chen, Chi-Yuan; Chen, Chin-Chuan; Chuang, Wen-Yu; Leu, Yann-Lii; Ueng, Shir-Hwa; Hsueh, Chuen; Yeh, Chau-Ting; Wang, Tong-Hong (Frontiers in Oncology, 2020)
Abnormal histone deacetylase (HDAC) expression is closely related to cancer development and progression. Many HDAC inhibitors have been widely used in cancer treatment; however, severe side effects often limit their clinical application. In this study, we attempted to identify natural compounds with HDAC inhibitory activity and low physiological toxicity and explored their feasibility and mechanisms of action in liver cancer treatment. A yeast screening system was used to identify natural compounds with HDAC inhibitory activity. Further, western blotting was used to verify inhibitory effects on HDAC in human liver cancer cell lines. Cell functional analysis was used to explore the effects and mechanisms and the in vitro results were verified in BALB/c nude mice. We found that hydroxygenkwanin (HGK), an extract from Daphne genkwa, inhibited class I HDAC expression, and thereby induced expression of tumor suppressor p21 and promoted acetylation and activation of p53 and p65. This resulted in the inhibition of growth, migration, and invasion of liver cancer cells and promoted cell apoptosis. Animal models revealed that HGK inhibited tumor growth in a synergistic manner with sorafenib. HGK inhibited class I HDAC expression and had low physiological toxicity. It has great potential as an adjuvant for liver cancer treatment and may be used in combination with anticancer drugs like sorafenib to improve therapeutic efficacy.